Studi Pengaruh Jumlah Cluster pada Wireless Sensor Network (WSN) menggunakan Protokol Low Energy Adaptive Clustering Hierarchy (LEACH) - Risqi Nuril Aimah; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
One of the problems in Wireless Sensor Network (WSN) is the use of energy.WSN is a network that connects devices, such as sensor node, router and sink node. This problem occurs because the power supply used for each node only uses battery in every process such as sending and receiving data, so the energy reserves are very limited. Therefore, the use of energy in the WSN sensor node becomes efficient by using the Low Energy Adaptive Clustering Hierarchy (LEACH) protocol. The performance of the LEACH routing protocol is influenced by several factors such as the number of node and the number of cluster. This study focuses on determining the performance of the LEACH routing protocol to determine the effect of variations in the number of cluster with the test parameters of Average Energy, Packet Delivery Ratio (PDR), Average Delay and Average Throughput on WSN. Based on the test results of Average Energy, Packet Delivery Ratio (PDR), Average Delay and Average Throughput obtained, the number of cluster 1 has the smallest Average Energy. The Packet Delivery Ratio test was found for the number of cluster 4 to get the highest result. Throughput testing for the number of cluster 4 get the highest Average Troughput results.